The ends of performance - Phelan, Peggy; Lane, Jill (New York : New York University Press, 1998)
Introduction : the ends of performance / Peggy Phelan ## History, memory, necrophilia / Joseph Roach ## Seeing death : the photography of David Wojnarowicz / Robert Sember ## On colonial forgetting : the conquest of New Mexico and its Historia / Jill Lane ## Perfoming writing / Della Pollock ## Teaching "experimental critical writing" / Eve Kosofsky Sedgwick ## This black body in question / Amanda Denise Kemp ## A fool's discourse : the buffoonery syndrome / Mady Schutzman ## Spare parts / Theresa M. Senft ## AmeRican accents syncopate the state / Doris Sommer ## Border watching / Diana Taylor ## Staging crisis : twin tales in moving politics / Randy Martin ## Bodies outside the state : Black British women playwrights and the limits of citizenship / May Joseph ## Genre trouble : (the) butler did it / Jon McKenzie ## The mirrored stage : reflections on the presence of Sylvia [Bataille] Lacan / Jamer Hunt ## Virtual criticism and the dance of death / Marcia B. Siegel ## The bed took up most of the room / Jane Blocker ## Orlan's performative transformations of subjectivity / Tanya Augsburg ## Intervention / Orlan ## Of mice, bugs and women / Deb Margolin ##What is performance studies anyway? / Richard Schechner
Includes bibliographical references and index.
boek